2020
DOI: 10.1080/01431161.2020.1800125
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation mapping of No Name Key, Florida using lidar and multispectral remote sensing

Abstract: LIght Detection And Ranging (lidar) data have been widely used in the areas of ecological studies due to lidar's ability to provide information on the vertical structure of vegetation in wildlife habitats. The overall objective of this project was to map the vegetation on No Name Key, Florida where endangered wildlife species reside using publicly available remote sensing data such as lidar data and high resolution aerial images (including National Agricultural Imagery Program (NAIP) images). The methods invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Based on the analysis of the publications searched, it is known that the current research on multispectral in agriculture is mainly focused on vegetation index ( Chang et al, 2020 ; Kim et al, 2020 ; Mazzia et al, 2020 ), land cover ( Laamrani et al, 2020 ), vegetation classification ( Gibson et al, 2004 ), crop estimation ( Zhou et al, 2017 ), drought monitoring ( Periasamy and Shanmugam, 2016 ), and environmental change ( Brook et al, 2020 ). Among them, the studies related to vegetation indices involves the most papers.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the analysis of the publications searched, it is known that the current research on multispectral in agriculture is mainly focused on vegetation index ( Chang et al, 2020 ; Kim et al, 2020 ; Mazzia et al, 2020 ), land cover ( Laamrani et al, 2020 ), vegetation classification ( Gibson et al, 2004 ), crop estimation ( Zhou et al, 2017 ), drought monitoring ( Periasamy and Shanmugam, 2016 ), and environmental change ( Brook et al, 2020 ). Among them, the studies related to vegetation indices involves the most papers.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies highlight higher accuracy in detection and vegetation mapping using LiDAR combined with high-resolution multispectral imagery (Asner et al 2008, Kim et al 2020, Liang et al 2020. LiDAR uses laser light to derive three-dimensional information (Popescu 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated its superiority for high-dimensional input data such as hyperspectral and multi-source data , even with limited training data (Ham et al 2005, Chan et al 2012, Abdel-Rahman et al 2014, Jensen et al 2020, Shoot et al 2021. Kim et al (2020) conducted vegetation mapping with LiDAR and multispectral imagery using four different classification algorithms (Support Vector Machine (SVM), RF, ML, and Mahalanobis Distance). RF classification using NAIP-LiDAR stacked image provided the highest OA (75.7%).…”
Section: Introductionmentioning
confidence: 99%
“…These models usually contain at least one variable explaining tree height, another explaining canopy cover, and another that accounts for variation in the data, such as a height standard deviation variable [6,31,32]; however, the variables in these models may differ depending on the study site and the foliage type being measured [28,33,34]. Estimates of BA, volume, and AGB can also be acquired from non-parametric machine learning approaches such as random forest (RF), a machine learning algorithm that uses random and iterative samples of the data to produce regression trees and bootstraps data for robust predictive models [35][36][37].…”
Section: Introductionmentioning
confidence: 99%